Measuring intermediate outcomes of Liberia's DDRR program - Ian Levely (Charles University in Prague, Institute of Economic Studies (IES), 2012)
This paper analyzes data from a survey of ex-combatants in Liberia conducted in 2006 by Pugel (2006. 2007), with the goal of determining the effect that Liberia's Demobilization, Disarmament, Rehabilitation and Reintegration program had on participants' income and chances of finding employment. I estimate the effects on educational and geographic cohorts. As individuals did not enter or complete the program randomly, these estimates are biased. I use propensity score matching to obtain a more precise estimate. While the results indicate an increase in employment for those who complete the program, there is consistently no effect on income. These results have implications for both evaluating the outcomes in Liberia as well as assessing the integrated approach to ex-combatant reintegration that the program embodied.
Keywords: D74; O15; O17; 330; civil war; vocational training; post-conflict reintegration